Why people remain inactive during a crisis: Interpreting and dealing with a crisis within a broader social context. - Kim, Jarim (Health, Risk & Society)
Public inactivity has been addressed by scholars across different academic disciplines. Risk communication and behaviour change is difficult and costly due to limited attention to various messages in the public sphere. Crises pose particular challenges if organisations are to communicate effectively with the public to protect them from potential risks. The present study attempts to better understand what makes the public inactive when faced with a crisis. Specifically, I focus on how people perceive a crisis and the reasons they remain inactive during the crisis. Using 28 in-depth interviews with Korean citizens during two food-related crises, this study revealed that people interpreted the crisis within a broader social context, made underlying assumptions in understanding the crisis and believed what the media vividly showed. The findings also showed that people remained inactive because they avoided dealing with risks due to being distracted by their daily lives, they trusted social systems to manage the problem, and they felt they had high efficacy in resolving the crisis although they did not expect to make fundamental changes in the long-run.